Biological Diversity and Human Welfare - Chakrabarti, Kalyan (Indian Forester, 1994)
The paper describes the importance of in-situ conservation of biodiversity to ensure the natural process of evolution to continue without any hinderance. The results of Project Tiger areas with a concept of total ecosystem preservation in the core areas are worth mentioning here. The main reasons for the degradation of ecosystem are poverty and ignorance about the understanding the ecosystem. Therefore, people from all walks of life are to be involved in conservation education for the common benefit of mankind.